Analisis Komparatif Tingkat Pendapatan Petani Sayuran Di Kabupaten Tanah Datar Kec. X Koto Prov. Sumatera Barat (Studi Kasus Di Nagari Koto Laweh Dan Nagari Paninjauan) - Puti Mandasari; Nursiah Chalid; Eriyati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted on vegetables farm area in Tanah Datar district, Kec. X Koto, Nagari Koto Laweh and Nagari Paninjauan, West Sumatera. The aim of this research is to find out the different rate income between Nagari Koto Laweh and Nagari Paninjauan by looking at influece of Tumpang Sari plantation system, workers, and farmer's work hour in both Nagari. The amount of samples in this research are 40 families as respondent, and technique took the samples was by using purposive sampling. Analysis methode that used in this research is descriptive methode. Based on the research was found that different rate income between vegetable farmers in Nagari Koto Laweh and Nagari Paninjauan. Final income from total of all vegetable commodities that get by each farmer families is 223.270.221,1, per hectare per plantation season ( 11 months) or about 20.297.292,8 in a month. Where an total final income from all vegetable commodities that get by each farmer families in Nagari Paninjauan is Rp 341.040.910,9,- a month in a plantation season or about Rp 31.003.719,1,- in a month. That means there is found different final income per hectare in a year Rp 117.770.689,8 or Rp 10.706.426,3,-in a month. The factors that causing this different rate income are Tumpang Sari system and farmer's work hour.Keywords: production, cost, income